Migration Dynamics and New Trends in European (In)Security Crises, Challenges and Opportunities - IOV, Claudia Anamaria (2022)
In the 21st Century, migration-security relationship in Europe, inthe context of globalization, takes on new dimensions with amplereverberations on the societal, economic, demographic, political, militaryand social fields. The refugee crisis, East-West/South-North chaoticmigration, regional interethnic disputes, the “special operation” fromUkraine, became top priorities on the European security agenda. In thiscontext, the volume brings to the fore, through a multidisciplinaryanalysis, the “complicated” relationship between migration and(in)security with a special focus on the integration process of migrantsand refugees and the image of “ the other” (alterity).The book is part of a constructivist approach with a dynamicperspective on the political, social, economic, military and societal field,where the actors and the system structure are interconnected.